2013
DOI: 10.5090/kjtcs.2013.46.6.457
|View full text |Cite
|
Sign up to set email alerts
|

The Unusual Suspect: Anemia-induced Systolic Anterior Motion of the Mitral Valve and Intraventricular Dynamic Obstruction in a Hyperdynamic Heart as Unexpected Causes of Exertional Dyspnea after Cardiac Surgery

Abstract: Dynamic left ventricular (LV) outflow tract obstruction is a characteristic feature of hypertrophic cardiomyopathy; however, it can also occur in association with hyperdynamic LV contraction and/or changes in the cardiac loading condition, even in a structurally normal or near-normal heart. Here, we report a case of anemia-induced systolic anterior motion of the mitral valve and the resultant intraventricular obstruction in a patient who underwent coronary artery bypass grafting and suffered from anemia associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In contrast to the SAM after mitral valve repair, which is a relatively common postoperative manifestation [ 1 , 6 ], SAM that occurs after nonmitral cardiovascular surgery is still an exceptional entity [ 2 , 3 ] and more likely to be missed or not quickly detected as the primary cause of hemodynamic instability. In a patient who underwent a CABG surgery, the principal causes of hypotension would be poor contractility due to cardiac stunning or graft flow abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the SAM after mitral valve repair, which is a relatively common postoperative manifestation [ 1 , 6 ], SAM that occurs after nonmitral cardiovascular surgery is still an exceptional entity [ 2 , 3 ] and more likely to be missed or not quickly detected as the primary cause of hemodynamic instability. In a patient who underwent a CABG surgery, the principal causes of hypotension would be poor contractility due to cardiac stunning or graft flow abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…It has been sporadically reported that dynamic SAM occurred in patients with acute coronary syndrome [ 7 ], sepsis [ 8 ], and severe anemia [ 3 ]. Said and coworkers suggested that the thickening of the interventricular septum (bulging subaortic septum) was one of the most important factors of dynamic LVOT obstruction after mitral valve repair [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation